1995
DOI: 10.1897/1552-8618(1995)14[411:ioscoa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sediment Composition on Apparent Toxicity in a Solid-Phase Test Using Bioluminescent Bacteria

Abstract: Clean and spiked sediment formulations of various silt sand and clay sand ratios were tested for toxicity using a bioassay that utilizes bioluminescent bacteria Measured toxicities of clean and copper sulfate-spiked sediments were negatively but nonlinearly related with percent silt and percent clay, but no significant relationship existed between measured toxicity and sediment composition for methyl parathion-spiked formulations Results suggest that solid phase sediment bioassays using bio luminescent bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 1 publication
0
18
0
1
Order By: Relevance
“…Cu, Hg, Pb, Zn and ∑PAHs in F1 and with Cd and Pb in F3) and with OM (F1 and F3) and mud (F3) content. The relationship between Microtox® results and OM and mud content has been previously reported (Benton et al 1995;Ringwood et al 1997). It is difficult to establish differences among stations based on this test, as it showed toxicity in the majority of the stations.…”
Section: Discussionmentioning
confidence: 84%
“…Cu, Hg, Pb, Zn and ∑PAHs in F1 and with Cd and Pb in F3) and with OM (F1 and F3) and mud (F3) content. The relationship between Microtox® results and OM and mud content has been previously reported (Benton et al 1995;Ringwood et al 1997). It is difficult to establish differences among stations based on this test, as it showed toxicity in the majority of the stations.…”
Section: Discussionmentioning
confidence: 84%
“…loss of bacteria adhering to the particles and filtered from the test suspension, such that a significant bias can occur in the interpretation of the results (Benton et al, 1995;Ringwood et al, 1997;Stronkhorst et al, 2003). Ringwood et al (1997) reported that a high rate of false positive results was obtained following exposure to estuarine sediments that were characterised by high silt-clay content.…”
Section: Discussionmentioning
confidence: 99%
“…In order to deal with interferences to the SPT, mainly caused by fine particles that cause loss of bacteria (Bulich et al, 1992;Benton et al, 1995;Ringwood et al, 1997), each harbour sample was compared with a reference sediment sample collected from a clean site on the northern Tyrrhenian coast. The reference sample was similar with respect to the particle size and mineralogical composition to the sediments collected in harbours.…”
Section: Microtox ® Assaymentioning
confidence: 99%